Leading learning among the indigenous orang asli students: setting the scene - Misnaton Rabahi; Hamidah Yusoff; Marinah Awang (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper highlights the initialising stage of a Grounded Theory research with a focus on how some students from the indigenous Orang Asli community survived the deficit theorizingthat rationalizes learning disengagement among them. Influenced by arguments of anti-deficit thinkers, this research seeks to understand the situation from the perspective ofstrength. Research sampling was purposeful, within the context of theoretical sampling following the Grounded Theory method. To-date, data have been gathered through unstructured interviews with sixteen (16) participants who have reached the tertiary level education. This paper however, presents the initial data gathered from fieldwork and interviews with the first participant, which sets the scene for the subsequent research process. The final findings are expected to provide an in-depth knowledge of the leading learning process among the successful Orang Asli students; providing lessons learnedfor students, parents, teachers, schools, community, and policy makers to consider for the betterment of theindigenous education. The study willcontribute to the body of literature that supports strength-based practice for the continuous improvement of the disadvantaged indigenous community.